Ixora apartment repair management system - Ho, Lai Ming; Saringat, Mohd Zainuri (Penerbit UTHM, 2021)
The current repair request management of the Ixora Apartment managed by the administrator using the paper-based repair request form. This management is inconvenient for users and may result in data loss. For the above reasons, a web-based repair management system was proposed for Ixora Apartment to manage their repair management system. This proposed project implemented using the waterfall model. The waterfall model consists of six phases which are requirement analysis, system design, implementation, testing, deployment, and maintenance. In this project, four phases will use to implement the Ixora Apartment Repair Management System. The phases used in this project are the requirement analysis phase, system design phase, implementation phase, and testing phase. This project target to help the requesters and staffs create and manage the repair request conveniently and effectively. The requesters can create a repair request anytime and anywhere without any consideration. Besides, requesters able to get the latest status of the requested repair request and provide feedback easily. Additionally, the administrator can manage the repair request effectively by accept, reject, or update the repair request. The focus of the Ixora Apartment Repair Management System project is to develop a web-based repair management system for the requesters and staffs of the Ixora Apartment to manage the repair request and to convert the paper-based repair management system to an online repair management system. Thereby, minimize human factor and limitation problems, and maximize convenience and working efficiency. Testing has conducted and summarized after the implementation phase. The overall results of the test case are in the pass state. All modules have presented and function according to the expected outcomes.